The Influence of Employee Performance and Service Quality on Customer Satisfaction at Bernard's Guesthouse Tuktuk Siadong Samosir - K Tarigan, Adrian; Saragih, JR; Wardati, Jumadiah; Nasution, Nurul Suci Anggraeni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the effect of employee performance and service quality on customer satisfaction at Bernard's Guesthouse Tuktuk Siadong Samosir. The research method used is descriptive quantitative method with data analysis, namely validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, simple linear regression analysis, multiple linear regression analysis, coefficient of determination (r2), and hypothesis testing. The population in this study were all employees at Bernard'S Guest House as many as 30 people. The data source of this research is primary data by using a research instrument in the form of a questionnaire. The results of this study indicate that partially employee performance variables (X1) and service quality variables (X2) have a significant positive effect on customer satisfaction (Y) at Bernard's Guesthouse Tuktuk Siadong Samosir.